Systematic Review of Problem Based Learning Student Worksheets for Developing Critical Thinking: Kajian Sistematis Lembar Kerja Peserta Didik Berbasis Problem Based Learning untuk Pengembangan Berpikir Kritis - Dewi, Citra Asmara; Khafid, Muhammad; Widiarti, Nuni; Yuwono, Agus (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education in the 21st century demands learning approaches that foster higher-order thinking skills. Specific Background: Problem-Based Learning (PBL) has been widely used to structure learning experiences that encourage critical thinking. However, learning media such as Student Worksheets (LKPD) require systematic evaluation to ensure their effectiveness. Knowledge Gap: Although many studies have developed PBL-based LKPD, there has been no comprehensive review analyzing publication trends, validity, practicality, and results from multiple studies. Aims: This study aims to synthesize findings from national studies on the development and implementation of PBL-based LKPD to train students’ critical thinking skills. Results: A total of 17 articles (2019–2025) were systematically reviewed. Most studies (88.24%) reported that PBL-based LKPD were valid, practical, and effective in fostering critical thinking, with publication trends increasing notably between 2023 and 2025. Novelty: This review applies the Systematic Literature Review method to provide a structured synthesis, identifying variations in research focus across educational levels. Implications: The findings support the strategic use of PBL-based LKPD as innovative learning media to cultivate critical thinking skills and inform future curriculum development and research. Highlight: PBL-based LKPD consistently validated as effective tools for critical thinking. Research focus varies by educational level, reflecting implementation stages. Publication trends reveal growing interest in innovative learning approaches. Keyword:Problem Based Learning, Student Worksheet, Critical Thinking Skills, Systematic Literature Review, Innovative Learning